Nursing Students’ Sociodemographic Characteristics and Consumer Preferences’ Prediction Level of Perceived Food Literacy - Duru, Sinan (Makara Journal of Health Research, 2025)
Background: Food literacy, which is a critical competency for nursing students, plays a pivotal role in promoting evidence-based nutrition behaviors and contributes effectively to public health. This study aimed to determine the level of perceived food literacy among nursing students. Methods: This cross-sectional study involved 488 nursing students from two universities in the south of Turkey. The research data were collected face to face via the Personal Information Form, the Consumer Preferences Form, and Self Perceived Food Literacy. The data was analyzed using the Independent Sample t Test, One Way ANOVA, and multiple linear regression. Results: The perceived food literacy of nursing students differed significantly by gender (p = 0.002), lifestyle (p = 0.001), smoking (p = 0.000), and paying attention to the expiration date (p = 0.000). The prediction level of perceived food literacy of nursing students' sociodemographic characteristics and consumer preferences was 31% (p = 0.000). There was a one standard deviation increase in the smoking and paying attention to the expiration date, a change of 0.143 and -0.240 standard deviations occurs in the SPFL total score average, respectively (p = 0.003; p = 0.000). Conclusions: This study may contribute to the development of evidence-based strategies in nursing education to improve food literacy of nursing students in clinical and community settings.